STRATEGI PENINGKATAN PARTISIPASI MASYARAKAT DALAM INOVASI DAERAH KABUPATEN BANGGAI - Irwan Moridu (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
The main objective of this research is to identify the supporting and inhibiting factors in community participation as well as strategies for increasing community participation in various innovative programs of the Banggai Regency Government. The research method uses descriptive method with the SWOT analysis method. Based on the results of the SWOT analysis the Regional Government of Banggai Regency has strengths that can be used in certain strategies and utilizes the right opportunities and simultaneously minimizes or avoids existing weaknesses and threats. This position is very beneficial for the Regional Government of Banggai Regency by improving conditions above the average capability so that the Regional Government of Banggai Regency can minimize weaknesses and take advantage of the role of the community in utilizing regional innovations. This is in line with the Vision of the Banggai Regency which is to realize the Banggai Regency as the Center for Agricultural and Maritime Economic Growth Based on Local Wisdom and Culture, this can be achieved with the participation of the community so that the Banggai Regency Vision can be realized in the future.